Significance of Pharmacy Education for BHMS Students (Homoeopathy for All, 2024)
Homoeopathy is one of the oldest  originated complementary and  alternative medicine which was  introduced in Europe more than  200 years ago. Homoeopathy was  first introduced in India by the  Germans in the year 1810 and it  started becoming popular in the year  1839. The demand of homoeopathic  remedies is on an unprecedented rise  which has attracted the attention of  the general masses. The Government  of India is serious about the quality  of homoeopathic education,  research in homoeopathy, quality  of homoeopathic medicines and its  proper regulation for manufacturing  and sale.
Keywords: India; essential; manufacture